Co-occurrence of mcr-1 mediated colistin resistance and β-lactamase-encoding genes in multidrug-resistant Escherichia coli from broiler chickens with colibacillosis in Tunisia. (September 2020) - Dhaouadi, Sana; Soufi, Leila; Hamza, Amani; Fedida, Didier; Zied, Chtioui; Awadhi, Emna; Mtibaa, Mohamed; Hassen, Bilel; Cherif, Ameur; Torres, Carmen; Abbassi, Mohamed Salah; Landolsi, Ramzi Boubaker
Highlights: A high level of MDR E. coli (96%) in broiler chickens with colibacillosis in three Tunisian poultry farms. This is the first report of the co-carriage of bla CTX-M-1, bla TEM, bla SHV β-lactamases, and mcr-1 -encoding genes in E. coli from chickens with colibacillosis in Tunisia. Colistin-resistant and ESBL avian pathogenic E. coli of the B2 phylogroup were detected. Clonal dissemination of ESBL- mcr-1 harbouring E. coli isolates occurred within two farms in Tunisia. We detected four ST lineages—ST3882, ST4187, ST5693, and ST8932—among ESBL- and mcr-1 -carrying E. coli isolates. Abstract: Objectives: Colibacillosis caused by avian pathogenic Escherichia coli (APEC) is considered a major hindrance in poultry farming worldwide. This study aimed to characterize the genetic content and the relatedness between multidrug-resistant E. coli isolates from broiler chickens died due to colibacillosis from three farms from Tunisia. Methods: One hundred samples were collected from chickens' fresh carcasses from three poultry farms in Tunisia. E. coli isolation and identification were performed. Then, antimicrobial susceptibility regarding antibiotics, the ability to produce β-lactamases and minimum inhibitory concentration for colistin were determined according to Clinical and Laboratory Standards Institute guidelines. β-Lactam and non-β-lactam antimicrobial resistance genes, integrons, virulence genes, and phylogenetic groups were investigated using polymerase chain reaction. The genetic relatedness of the E. coli isolates was analysed by pulsed field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). Results: A high infection rate of E. coli (50%) in infected organs of chickens was observed. The majority of E. coli isolates were multidrug resistant (96%); among them, 24% were colistin resistant and 30% were ESBL producing. Seven of 12 colistin-resistant isolates harboured the mcr-1 gene; among them, 10 were ESBL producing and carried bla CTX-M-1, bla TEM, and bla SHV β-lactamase-encoding genes. E. coli isolates were assigned to different phylogroups but most of them (74%) belonged to the pathogenic phylogroup B2. Molecular typing by PFGE showed that some E. coli isolates harbouring ESBL- mcr-1 genes were clonally related. MLST revealed the presence of four different ST lineages among ESBL- and mcr-1 -carrying E. coli : ST4187, ST3882; ST5693, and ST8932 with clonal dissemination of E. coli ST4187 between two of the farms. Conclusion: This is the first report of ESBL- mcr-1 -carrying E. coli isolates of a clinically relevant phylogenetic group (B2) from chickens that died due to colibacillosis in Tunisian poultry farms.